Motion cueing algorithm for high performance driving simulator using yaw table. Issue 1 (July 2017) - Fang, Z.; Tsushima, M.; Kitahara, E.; Machida, N.; Wautier, D.; Kemeny, A.
Abstract: In the last decade, MPC based motion cueing algorithm (MCA) has been successfully applied in driving simulator. Generally, in the conventional MPC based MCA, the multi-axes motion cueing problem is dealt with separately using 2DOF (linear + tilt motions) optimization technique. In the current study, a multi-axes coupled 4DOF optimization algorithm is proposed which completes the lack of efficient motion cueing algorithm for X-Y based driving simulator using yaw table.